A Escola Politécnica e a transformação de São Paulo - Padilha, Rodrigo Bastos (2015)
Between 1870 and 1920, São Paulo State went through an intense transformation process that turned the State into the economically most developed State in the Federation. This thesis identified the main factors that contributed to the success in the State development: favorable geographic characteristics; wealth accumulation favored through coffee plantations; availability of an extensive railway system connected to a deep-water port; relatively cheap hydro-electricity; labor coming from immigration; and a minimum local technological basis. It is not trivial to quantify the weight to be given to each of the mentioned factors related to the São Paulo development, however it may be stated that all countries that went through an accelerated development process had good engineering faculties. The development of São Paulo relied on its initial stage on four institutions, namely: the Arts and Crafts Lyceum; the Polytechnic School of São Paulo; the Mackenzie Engineering College; and the Institute of Technological Research (IPT). The laboratories of the Polytechnic School and later of the IPT conducted the first studies and tests that provided subsidies to the local engineering projects. The academic staff and the graduated engineers from the Polytechnic School created the first genuine national engineering bureaus in the State. Several founded or became partners in industrial and commercial enterprises. The participation of the Polytechnic School and of the graduated engineers in the development of the starting-up of chemical, metallurgical and transformation industries has been decisive to the industrialization of the State of São Paulo and of Brazil